Countering Extremists on Social Media: Challenges for Strategic Communication and Content Moderation. Issue 1 (16th March 2020) - Ganesh, Bharath; Bright, Jonathan
Abstract : Extremist exploitation of social media platforms is an important regulatory question for civil society, government, and the private sector. Extremists exploit social media for a range of reasons—from spreading hateful narratives and propaganda to financing, recruitment, and sharing operational information. Policy responses to this question fit under two headings, strategic communication and content moderation. At the center of both of these policy responses is a calculation about how best to limit audience exposure to extremist narratives and maintain the marginality of extremist views, while being conscious of rights to free expression and the appropriateness of restrictions on speech. This special issue on "Countering Extremists on Social Media: Challenges for Strategic Communication and Content Moderation" focuses on one form of strategic communication, countering violent extremism. In this editorial we discuss the background and effectiveness of this approach, and introduce five articles which develop multiple strands of research into responses and solutions to extremist exploitation of social media. We conclude by suggesting an agenda for future research on how multistakeholder initiatives to challenge extremist exploitation of social media are conceived, designed, and implemented, and the challenges these initiatives need to surmount. Abstract : 极端分子对社交媒体平台的滥用是公民社会、政府和私人部门关注的一个重要监管疑问。极端分子出于一系列原因滥用社交媒体: 从散播仇恨叙事和宣传, 到金融、招聘和分享操作信息。该疑问所获得的政策响应有两个方面: 战略传播和内容审核。这两类政策响应的核心是计算如何最大程度地限制受众接收到极端主义叙事, 保持极端主义观点的边缘性, 同时考虑自由言论权和言论限制的适当性。本期特刊主题为《打击社交媒体极端主义: 战略传播与内容审核面临的挑战》, 聚焦于战略传播的一种形式, 即反暴力极端主义(CVE)。本期社论中, 我们探讨了CVE这种措施的背景和有效性, 同时介绍五篇文章, 后者就有关极端分子滥用社交媒体的响应与解决措施提出了多个研究。我们的结论为有关如何感知、设计和执行"拒绝极端分子滥用社交媒体"的多个利益攸关方倡议的未来研究提出一项议程, 并提出了这些倡议需克服的挑战。 Abstract : La explotación extremista de las plataformas de redes sociales es una cuestión regulatoria importante para la sociedad civil, el gobierno y el sector privado. Los extremistas explotan las redes sociales por una variedad de razones, desde difundir narrativas de odio y propaganda hasta financiar, reclutar y compartir información operativa. Las respuestas de política a esta pregunta encajan en dos encabezados: comunicación estratégica y moderación de contenido. En el centro de ambas respuestas políticas se encuentra un cálculo sobre la mejor manera de limitar la exposición de la audiencia a las narrativas extremistas y mantener la marginalidad de los puntos de vista extremistas, mientras se tiene conciencia de los derechos a la libertad de expresión y la idoneidad de las restricciones al discurso. Este número especial sobre "Contrarrestar a los extremistas en las redes sociales: desafíos para la comunicación estratégica y la moderación de contenido" se centra en una forma de comunicación estratégica, contrarrestar el extremismo violento (CVE). En este editorial discutimos los antecedentes y la efectividad de este enfoque e introducimos cinco artículos que desarrollan múltiples líneas de investigación sobre respuestas y soluciones a la explotación extremista de las redes sociales. Concluimos sugiriendo una agenda para futuras investigaciones sobre cómo se conciben, diseñan e implementan las iniciativas de múltiples partes interesadas para desafiar la explotación extremista de las redes sociales, y los desafíos que estas iniciativas deben superar.